Effect of intravitreal aflibercept on corneal endothelial cells: a 6-month follow-up study - Muto T (Dove Medical Press, 2019)
Tetsuya Muto, Shigeki Machida Department of Ophthalmology, Dokkyo Medical University Saitama Medical Center, Koshigaya, Japan Purpose: To determine the effect of intravitreal aflibercept injection on the corneal endothelium in patients with diabetic or cystoid macular edema caused by retinal vein occlusion. Material and methods: Forty-six eyes of 44 consecutive patients (27 men, 17 women; age range: 55–88 years) were evaluated. All participants initially received a single intravitreal injection of aflibercept (2 mg in 0.05 mL), followed by pro re nata use and underwent central corneal specular microscopy before the injection and at 1, 3 and 6 months after the first injection during a 6-month follow-up period. The endothelial cell density (ECD), average cell size (AVG), standard deviation of cell size (SD), coefficient of variation of cell size (CoV), maximum of cell size (MAX), minimum of cell size (MIN) and percentage of hexagonal cells (Hex%) were analyzed and the central corneal thickness (CCT) was measured. Results: No significant differences in the ECD, AVG, SD, CoV, MIN, Hex% and CCT were observed between measurements obtained before and 1, 3 and 6 months after the first injection. However, the MAX measured before injection differed significantly from the values measured at 1, 3 and 6 months after the first injection (P=0.033). An average of 1.43±0.58 intravitreal aflibercept injections were administered per patient. Conclusion: These study findings indicate that the intravitreal administration of aflibercept (2 mg) might very slightly alter the corneal endothelium within 6 months of the first injection. Keywords: corneal endothelium, macular edema, retinal vein occlusion, vascular endothelial growth factor